The Beauty of Functional Code Essays Dedicated to Rinus Plasmeijer on the Occasion of His 61st Birthday - Achten, Peter; Koopman, Pieter (Programming and Software Engineering, 2013)
This Festschrift has been published in honor of Rinus Plasmeijer, to celebrate the combined occasion of his 61st birthday and the 25th Symposium on Implementation and Application of Functional Languages, IFL 2013, held in Nijmegen, The Netherlands, in August 2013. Rinus Plasmeijer was the main designer of the lazy functional programming language "Clean" and has always been the leader of the associated research team. He has played a decisive role in making the Radboud University of Nijmegen an important center of research in functional programming by organizing and hosting the first few IFL symposia in Nijmegen. This Festschrift contains 19 scientific essays written by former PhD students of Rinus Plasmeijer and researchers in the field of functional programming who have collaborated with him. The authors write about the influence the beauty of functional programming has had or still has on their work.